PENGARUH INVESTASI, KONSUMSI RUMAH TANGGA DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN BARAT - Anggatia Ariza (Journal of Islamic Economy and Business (JIsEB), 2024)
Each Country basically has a goal in economic development that is advanced in order to achieve the level of well-being of society and to create a better economic, social, political system in the future. Economic development strives to achieve high economic growth that ultimately enables the improvement of the living standards and welfare of all people. This research aims to find out; 1) the influence of investment on economic growth in West Kalimantan, 2) the influence of household consumption on economic growth in West Kalimantan, 3) the influence of government spending on economic growth in West Kalimantan, 4) the influence of investment, household consumption and simultaneous government spending on economic growth. The method used in this study is a descriptive method with a quantitative approach. The data collection technique used is an explanatory technique by explaining causation. The data analysis technique used in the data analysis technique used is the regression analysis of the data panel which is a combination of time series and cross section. The results of this study show that 1) Variable investment has a positive influence and a significant value of 0.010 on economic growth in West Kalimantan. 2) Household consumption variables have a positive effect and a significant value of 0.013 on economic growth. 3) Variable government spending has a positive effect and a significant value of 0.000 on economic growth. 4) Variable investment, household consumption and government spending have a significant impact on economic growth